NANOCOMPOSITION OF HYDROXYLAPATITE FROM CORTICAL BONE TISSUE - A.A. Bibko; D.V. Lychagin; O.V. Bukharova; E.A. Kostrub; M.O. Khrushcheva (Минералогия)
Hydroxylapatite is one of the main components of bone tissue. In combination with collagen, it provides unique strength properties of the bone. The nanostructure of bone tissue (its composition) remains a matter of debate. In this work, we studied the cortical bone tissue of rats using transmission electron microscopy (TEM) and X-ray diffraction. According to the results of the Scherrer method, the size of hydroxylapatite crystallites is 8.8 × 4.0 nm. The TEM showed the presence of crystalline hydroxyapatite areas in the interfibrillary space of collagen with the sizes ranging from 10 × 5 to 50 × 10 nm. These areas are the crystalline aggregates with a subblock structure, which is expressed in different orientations of axis c. No amorphous substance in bone tissue was identified using electron nanodiffraction.